2013
DOI: 10.1016/j.gene.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding motif and target genes of the imprinted transcription factor PEG3

Abstract: The Peg3 gene is expressed only from the paternally inherited allele located on proximal mouse chromosome 7. The PEG3 protein encoded by this imprinted gene is predicted to bind DNA based on its multiple zinc finger motifs and nuclear localization. In the current study, we demonstrated PEG3’s DNA-binding ability by characterizing its binding motif and target genes. We successfully identified target regions bound by PEG3 from mouse brain extracts using chromatin immunoprecipitation analysis. PEG3 was demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 34 publications
10
86
0
Order By: Relevance
“…6I). We note that a recent study has identified a Peg3-specific DNAbinding motif (42), and indeed we found a single minimal consensus sequence for Peg3 (TGGCT) at −604 bp relative to the transcription start site. Collectively, these results support the notion that decorin signals through VEGFR2 in endothelial cells and corroborate the binding studies discussed above.…”
Section: Decorin Requires Vegfr2 For Its Downstream Signaling Andsupporting
confidence: 75%
“…6I). We note that a recent study has identified a Peg3-specific DNAbinding motif (42), and indeed we found a single minimal consensus sequence for Peg3 (TGGCT) at −604 bp relative to the transcription start site. Collectively, these results support the notion that decorin signals through VEGFR2 in endothelial cells and corroborate the binding studies discussed above.…”
Section: Decorin Requires Vegfr2 For Its Downstream Signaling Andsupporting
confidence: 75%
“…18 PW1 has also been shown to function as a transcription factor with a DNA-binding motif regulating a large array of genes involved in metabolic homeostasis. 19 Moreover, PW1 expression is required for the myogenic and migratory capacities of both mouse and human mesoangioblasts, reinforcing the relevance of PW1 to identify competent mesoangioblasts before their use in stem cell-mediated therapeutic applications. 20 Given the distribution of PW1 expression in a wide array of adult somatic stem cells and the role of PW1 in cell stress responses, we investigated whether PW1…”
mentioning
confidence: 93%
“…9,10 Recent studies confirmed that PEG3 indeed binds to a large number of genomic targets as a DNA-binding protein. 7 According to the results, PEG3 functions as a transcriptional repressor for these downstream genes. 7 In particular, PEG3 binds to its adjacent imprinted gene, maternally expressed Zim1.…”
Section: Introductionmentioning
confidence: 98%
“…5,6 Some imprinted genes are also known to encode DNA-binding proteins, such as Zac1 and Peg3. 7,8 The DNA-binding protein encoded by Zac1 binds to the 3 0 enhancer of H19 as a transcriptional activator, suggesting a functional connection between the 2 imprinted genes, paternally expressed Zac1 and maternally expressed H19. 8 Detailed surveys further revealed that many imprinted genes behave coordinately in response to environmental and developmental cues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation